Developing Concepts and Generalizations to Build Algebraic Thinking: The Reversibility, Flexibility, and Generalization Approach. (May 2015) - Dougherty, Barbara; Bryant, Diane Pedrotty; Bryant, Brian R.; Darrough, Rebecca L.; Pfannenstiel, Kathleen Hughes
Many students with learning disabilities (LD) in mathematics receive their mathematics education in general education inclusive classes; therefore, these students must be capable of learning algebraic concepts, including developing algebraic thinking abilities, that are part of the general education curriculum. To help students develop algebraic thinking, teachers should ask questions in different ways to promote the ability to think algebraically. This article describes three types of questions—reversibility, flexibility, and generalizations—which support the acquisition of broader concepts leading to algebraic thinking. Examples of the question types within the contexts of rational numbers and integers are provided to assist teachers in creating similar questions for teaching mathematics to students with LD.